(3CSeGA QLGd GdeTcGIs - (3GdJHQjRj , eMeO Hf YHO Gddg GdNWjH GdYeQj, hdj GdOjf CHh YHO Gddg,J (B741 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG GdcJGH aj CSeGA GdQLGd eTJed Ydi HGHjf , GdHGH GdChd ai PcQ GdUMGHI eef dg PcQCh QhGjI ai cJGH GdeTcGI eQJH Ydi MQha GdJgLi s
(3BNQgG (B:s
(3haQZJ jhe GdLeYI ef YTQjf QLH SfI CQHYjf hSHYeGFI ef LeYI hJT(B>(3jH hGfG CVYa GdYHGO eMeO Hf YHOGddg GdNWjH Hf eMeO HeYGhfI heYGVOI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B211s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B195 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B262 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B29 s
(3eUOQ GbJfGA GdCUd (B:s
(3QhGb GdThGe (B- (3GdCRgQ (B((3oeUWdM GdMOjK (B284) s
Keywords: (3GdJGQjNs